Recent Progress on Fabrication of Thermal Conductive Aluminum Nitride Fibers - SHEN Zhuoer; REN Song; GE Can; ZHAO Haoyue; HAN Mengyao; FANG Jian (东华大学学报（英文版）, 2023)
TS102.4; Among nitride fibers,aluminum nitride(AlN)fibers have been developed for various advanced applications due to their mechanical flexibility,high thermal conductivity,and excellent electrical insulation and chemical stability.This article presents an overview on the recent progress of AlN fibers.The properties of AlN,particularly the thermal conductivity of AlN in polymer matrix composites are introduced.Afterward,two major approaches,carbothermal reduction and nitriding polycrystalline alumina fiber,for the preparation of AlN fibers are discussed.The carbothermal reduction includes electrospinning,solution blow spinning,and chemical vapor deposition.Furthermore,some perspectives on the future directions for the preparation and application of fibrous AlN are highlighted.This review is expected to provide readers with valuable guidance on the preparation of AlN fibers and inspire researchers to explore more potential applications.